2018
DOI: 10.1038/s41586-018-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Coherent encoding of subjective spatial position in visual cortex and hippocampus

Abstract: A major role of vision is to guide navigation, and navigation is strongly driven by vision. Indeed, the brain's visual and navigational systems are known to interact, and signals related to position in the environment have been suggested to appear as early as in the visual cortex. Here, to establish the nature of these signals, we recorded in the primary visual cortex (V1) and hippocampal area CA1 while mice traversed a corridor in virtual reality. The corridor contained identical visual landmarks in two posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
235
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(271 citation statements)
references
References 46 publications
35
235
1
Order By: Relevance
“…We discovered the predominant form of neural dynamics in all areas and layers to be the sequential activation of cells. This resembles place cells in the hippocampus (Moser, Kropff, and Moser 2008) , and place preferences have been reported by others in V1 (Saleem et al 2018) . However, most cells were preferentially active on either right-or left-choice trials, a phenomenon previously reported in the PPC (Harvey, Coen, and Tank 2012;Morcos and Harvey 2016) .…”
Section: Introductionsupporting
confidence: 83%
“…We discovered the predominant form of neural dynamics in all areas and layers to be the sequential activation of cells. This resembles place cells in the hippocampus (Moser, Kropff, and Moser 2008) , and place preferences have been reported by others in V1 (Saleem et al 2018) . However, most cells were preferentially active on either right-or left-choice trials, a phenomenon previously reported in the PPC (Harvey, Coen, and Tank 2012;Morcos and Harvey 2016) .…”
Section: Introductionsupporting
confidence: 83%
“…Our observations of sequential dynamics in all areas are amongst a growing number of such for the mouse neocortex [53][54][55][56][57][58] . These phenomena are reminiscent of place 76 or time [77][78][79] cells in the hippocampus, which are also known to jointly encode a variety of other spatial and nonspatial factors.…”
Section: Discussionmentioning
confidence: 76%
“…We believe these two options are not exclusive and the underlying processes might strongly interact in our naturalistic task. Locomotion and world-centered location (Fournier et al, 2019;Saleem et al, 2018) have for example been shown to modulate EVC activity in rodents. Here, we observed that locomotion had a positive effect on model performance in EVC and RSC, suggesting stronger directional tuning in these regions during running (Fig.…”
Section: Visual Information and Head Directionmentioning
confidence: 99%
“…Areas such as the PHG code direction even in the absence of visual experience (Bellmund et al, 2016). In addition, shared information and activity covariations between the EVC and the hippocampal formation suggest that early perceptual processing could well be modulated by higher-level cognitive processes (Bosch et al, 2014;Fournier et al, 2019;Hindy et al, 2016;Kok and Turk-Browne, 2018;Meister and Buffalo, 2016;Nau et al, 2018a;Saleem et al, 2018).…”
Section: Visual Information and Head Directionmentioning
confidence: 99%